Palladium-catalyzed oxidative cyclization of ?-allenols in the presence of TBN: access to 3(2H)-furanones - Ghotekar, Ganesh S.; Shinde, Ravi A.; Saswade, Sagar S.; Muthukrishnan, M. (Journal of Organic Chemistry, 2023)
A new palladium-catalyzed oxidative cyclization of alpha-allenols is described. The readily accessible alpha-allenols participate in intra-molecular oxidative cyclization in the presence of TBN to grant access to multisubstituted 3(2H)-furanones, which are common motifs in several biologically important natural products and pharmaceuticals.
Keywords: Alternatively; conditions; cumbersome workup; intramolecular electrophilic; multiple reaction steps; noted examples